Electrochemical performance of NASICON type carbon coated LiTi2(PO4)3 with a spinel LiMn2O4 cathode - Aravindan, Vanchiappan (2013)
NASICON type LiTi2(PO4)3 particles are synthesized by a modified pechini type polymerizable complex method at 1000 °C in an air atmosphere. The synthesized LiTi2(PO4)3 particles are ball milled and subsequently carbon coated from the carbonization of glucose (C–LiTi2(PO4)3). Li-insertion properties are evaluated in half-cell configurations (Li/C–LiTi2(PO4)3) and delivered an initial discharge capacity of 117 mAh g−1 at a current density of 15 mA g−1. Carbon coating alleviates the severe capacity fading of LiTi2(PO4)3 during cycling. A full-cell with an operating potential of 1.5 V is constructed employing C–LiTi2(PO4)3 as the anode with a spinel cathode, LiMn2O4, which delivered the first discharge capacity of 103 mAh g−1 at current density of 150 mA g−1. The LiMn2O4/C–LiTi2(PO4)3 cell retains 72% of initial discharge capacity after 200 cycles and the results suggest that, the full-cell can be used for miniature applications by replacing other rechargeable systems like lead–acid, Ni–Cd and Ni–MH.